Airway mucus, inflammation and remodeling: emerging links in the pathogenesis of chronic lung diseases - Zhou-Suckow, Zhe; Dürr, Julia; Hagner, Matthias; Agrawal, Raman; Mall, Marcus A. (Cell & tissue research, 2017)
Airway mucus obstruction is a hallmark of many chronic lung diseases including rare genetic disorders such as cystic fibrosis (CF) and primary ciliary dyskinesia, as well as common lung diseases such as asthma and chronic obstructive pulmonary disease (COPD), which have emerged as a leading cause of morbidity and mortality worldwide. However, the role of excess airway mucus in the in vivo pathogenesis of these diseases remains poorly understood. The generation of mice with airway-specific overexpression of epithelial Na+ channels (ENaC), exhibiting airway surface dehydration (mucus hyperconcentration), impaired mucociliary clearance (MCC) and mucus plugging, led to a model of muco-obstructive lung disease that shares key features of CF and COPD. In this review, we summarize recent progress in the understanding of causes of impaired MCC and in vivo consequences of airway mucus obstruction that can be inferred from studies in βENaC-overexpressing mice. These studies confirm that mucus hyperconcentration on airway surfaces plays a critical role in the pathophysiology of impaired MCC, mucus adhesion and airway plugging that cause airflow obstruction and provide a nidus for bacterial infection. In addition, these studies support the emerging concept that excess airway mucus per se, probably via several mechanisms including hypoxic epithelial necrosis, retention of inhaled irritants or allergens, and potential immunomodulatory effects, is a potent trigger of chronic airway inflammation and associated lung damage, even in the absence of bacterial infection. Finally, these studies suggest that improvement of mucus clearance may be a promising therapeutic strategy for a spectrum of muco-obstructive lung diseases.